Experimental and numerical assessment of confined infill walls with openings and textile-reinforced mortar - Furtado, André (2021)
This work's primary objective is to present an experimental campaign, comprised of three full-scale in-plane tests. It was assessed the effect of the openings (central window) and of using textile-reinforced mortar strengthening. The slenderness is also studied by comparing the results herein obtained with other test existing in the literature. The masonry infill walls were built with horizontal hollow clay bricks. All the tests consisted of applying cyclic (loading-unloading-reloading) history of imposed displacements in the in-plane direction employing a top horizontal load. The mechanical properties of the adopted materials are characterized and presented. The results will be presented in terms of in-plane force-displacement responses, damage evolution and energy dissipation capacity. A literature review of numerical modelling approaches to simulate the masonry infill walls seismic behaviour was provided after that. In the end, the experimental tests were simulated in the software OpenSees through a simplified modelling approach. The openings reduced the in-plane maximum strength and energy dissipation capacity by about 40% and 18%, respectively. On the other hand, the textile-reinforced mortar increased the initial stiffness, maximum peak strength and energy dissipation capacity by about 31%, 15% and 38%, respectively.